Advanced concepts and solutions for geothermal heating applied in Oradea, Romania. (January 2017) - Antal, C; Popa, F; Mos, M; Tigan, D; Popa, B; Muresan, V
Abstract: Approximately 70% of the total population of Oradea benefits from centralized heating, about 55, 000 apartments and 159, 000 inhabitants are connected. The heating system of Oradea consists of: sources of thermal energy production (Combined heat and power (CHP) I Oradea and geothermal water heating plants); a transport network of heat; heat distribution network for heating and domestic hot water; substations, most of them equipped with worn and obsolete equipment. Recently, only a few heat exchangers were rehabilitated and electric valves were installed to control the water flow. After heat extraction, geothermal chilled waters from the Oradea area are: discharged into the sewer system of the city, paying a fee to the local water company which manages the city's sewers; discharged into the small river Peta; or re-injected into the reservoir. In order to ensure environmental protection and a sustainable energy development in Oradea, renewable sources of energy have been promoted in recent years. In this respect, the creation of a new well for geothermal water re-injection into the reservoir limits any accidental thermal pollution of the environment, while ensuring the conservation properties of the aquifer by recharging with geothermal chilled water. The paper presents the achievements of such a project whose aim is to replace thermal energy obtained from coal with geothermal heating. The novelty consists in the fact that within the substation we will replace old heat exchangers, circulation pumps and valves with fully automated substations operating in parallel on both a geothermal system and on a primary heating system of a thermal plant.